A design approach for tunnels exposed to blast and fire. (June 2015) - Colombo, Matteo; Martinelli, Paolo; di Prisco, Marco
Abstract A design procedure based on a simplified FE model for underground tunnels subjected to internal explosion and possibly preceded by fire accidents is proposed in this article. The procedure can provide a valuable tool for designers who have to check the structural safety of a tunnel for the case of an internal blast event. The tunnel geometry considered is the same adopted for the metro line in Brescia, Italy. It has an internal diameter of about 8.15 m, is about 13.7 km long and is located about 23.1 m below the surface. Six segments and a smaller key segment (6+1) make up the tunnel. The ring has an average width of about 1.5 m. The FE model is first tested under static serviceability loads. Dynamic analyses are carried out in order to reproduce the blast scenario. The aim of this work is to generate pressure–impulse (p‐i) diagrams for underground tunnels for the case of internal explosion and pre‐explosion fire actions. An ultimate limit state criterion based on the eccentric ultimate flexural capacity and capable of including fire–blast interaction is introduced. An innovative layered precast tunnel segment solution made of different fibre‐reinforced cementitious composites is compared with a traditional solution with the lining section made of reinforced concrete. The potential applications of this new solution are also discussed in the paper.